2018
DOI: 10.1371/journal.pbio.2005264
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally derived macrophages modulate microglial function to reduce inflammation after CNS injury

Abstract: Infiltrating monocyte-derived macrophages (MDMs) and resident microglia dominate central nervous system (CNS) injury sites. Differential roles for these cell populations after injury are beginning to be uncovered. Here, we show evidence that MDMs and microglia directly communicate with one another and differentially modulate each other’s functions. Importantly, microglia-mediated phagocytosis and inflammation are suppressed by infiltrating macrophages. In the context of spinal cord injury (SCI), preventing suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
170
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(179 citation statements)
references
References 79 publications
8
170
0
1
Order By: Relevance
“…Furthermore, we examined monocyte/macrophage extravasation using CD11b. Consistent with previous reports that CD11b is able to label brain-resident microglia in addition to monocytes/macrophages [63,64], CD11b + cells (microglia) were detected in sham animals (Fig. 6e).…”
Section: Pko Mice Show Enhanced Inflammatory Cell Extravasation Aftersupporting
confidence: 92%
“…Furthermore, we examined monocyte/macrophage extravasation using CD11b. Consistent with previous reports that CD11b is able to label brain-resident microglia in addition to monocytes/macrophages [63,64], CD11b + cells (microglia) were detected in sham animals (Fig. 6e).…”
Section: Pko Mice Show Enhanced Inflammatory Cell Extravasation Aftersupporting
confidence: 92%
“…The primary injury causes a structural disturbance at the time of injury [3]. Then, a long-term secondary injury is considered a complicated and multifactorial stage that can cause a series of detrimental effects, including oxidative stress, inflammation, and mitochondrial dysfunction, which eventually contributes to neuronal apoptosis and inhibits axon regeneration and nerve recovery [4][5][6]. Therefore, effective prevention of detrimental secondary events by reduction of neuronal cell death and promotion of axon regeneration is a potential approach for improving functional recovery after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…We found that (a) AS-IV promotes autophagy and inhibits neuronal apoptosis after SCI. 8,[23][24][25] Numerous studies have targeted these two pathological processes for SCI therapy; however, barely any therapies could target both these two pathological processes. In our study, we found that AS-IV possesses 'one stone two birds' potential, which not only inhibits neuronal apoptosis but also suppresses neuroinflammation through inhibiting the mTORC1 signalling pathway (Figure 9).…”
Section: Discussionmentioning
confidence: 99%